A spectroscopic search for high-mass X-ray binaries in M31 - Williams, B. F.; Hatzidimitriou, D.; Green, J.; Vasilopoulos, G.; Covarrubias, R.; Pietsch, W. N.; Stiele, H.; Haberl, F.; Bonfini, P. (2014)
We present new optical spectroscopy of 20 candidate counterparts of 17 X-ray sources in the direction of the M31 disc. By comparing the X-ray catalogue from the XMM-Newton survey of M31 with star catalogues from the Local Group Galaxy Survey, we chose counterpart candidates based on optical colour and X-ray hardness. We have discovered 17 counterpart candidates with spectra containing stellar features. Eight of these are early-type stars of O or B type in M31, with hard X-ray spectra, making them good high-mass X-ray binary (HMXB) candidates. Three of these eight exhibit emission lines, which we consider to be the strongest HMXB candidates. In addition, our spectra reveal two likely Galactic cataclysmic variables, one foreground M star, two probable low-mass X-ray binaries related to M31 globular clusters, one emission-line region with an embedded Wolf-Rayet star and one newly discovered supernova remnant. Finally, two of the sources have stellar spectra with no features indicative of association with an X-ray source.
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - High Energy Astrophysical Phenomena; Astrophysics - Solar and Stellar Astrophysics; galaxies: individual: M31; galaxies: spiral; X-rays: binaries